Average Nutrient Content and Bulk Price of Byproduct Feeds Commonly Available to Florida Cattle Producers - John D. Arthington (EDIS, 2003)
This document is AN142, one of a series of the Animal Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date April 29, 2003.